BOOK REVIEW: Meerzon, Yana, and Stephen E. Wilmer (eds), The Palgrave Handbook of Theatre and Migration, Palgrave Macmillan, London/New York 2023 - Diakoumopoulou, Katerina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
BOOK REVIEW: Meerzon, Yana, and Stephen E. Wilmer (eds), The Palgrave Handbook of Theatre and Migration, Palgrave Macmillan, London/New York 2023